Multi-weatherability lignin monomer-based adhesive and preparation method thereof

By preparing random copolymer P(Cx-co-Gy), the problem of insufficient adhesion performance of lignin-based biomimetic adhesives in extreme environments was solved. High adhesion strength and good recyclability were achieved in environments such as humidity, extreme cold, and organic solvents, making it suitable for interfacial bonding of various materials.

CN121022307APending Publication Date: 2025-11-28BEIJING FORESTRY UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511164554.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing lignin-based biomimetic adhesives have insufficient adhesion performance in extreme environments such as underwater ultra-low temperatures and organic solvents, and are difficult to recycle and reuse.

Method used

Using wood G/S-lignin-degraded monophenols and plant shell C-lignin-degraded monophenols as raw materials, random copolymers P(Cx-co-Gy) were prepared through functionalization modification of degraded monophenols and free radical copolymerization. The repeating unit C accounted for 35-45%, and the number average molecular weight was 15×103-30×103. It has excellent adhesion and weather resistance.

Benefits of technology

It maintains high adhesion performance in extreme environments, including moisture, extreme cold, and organic solvents, with an adhesion strength of over 8.7 MPa. It has good recyclability and wide applicability, and is suitable for bonding various material interfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121022307A_ABST
    Figure CN121022307A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lignin-based adhesives, and particularly relates to a multi-weather-resistance lignin monomer-based adhesive and a preparation method thereof. The invention provides a strategy for preparing a high-performance bionic adhesive through depolymerization-derivation-copolymerization, which comprises the following steps: firstly, carrying out reduction catalytic degradation on wood G / S-lignin and plant shell C-lignin to respectively obtain monophenol compounds with specific structures, and then carrying out functional modification on the monophenol compounds to construct a monomer C and a monomer G with polymerizable activity; finally, the adhesive with excellent performance is prepared through a free radical copolymerization reaction, the adhesive shows excellent adhesion performance in humid, extremely cold and other environments, the underwater adhesion of the adhesive can reach 8.7 MPa, the adhesive strength of 7.2 MPa or above can still be kept under the ultralow temperature condition of-196 DEG C, and the adhesive strength can still reach 6 MPa after seawater and liquid nitrogen circulation treatment. The prepared adhesive is wide in raw material source, low in cost, excellent in weather resistance and high in industrial production value.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lignin-based adhesives, and particularly relates to a multi-weather-resistant lignin monomer-based adhesive and a preparation method thereof. BACKGROUND

[0002] In recent years, bio-inspired adhesives inspired by the mussel adhesion mechanism have been widely used in underwater repair, functional coatings, and high-performance composites due to their excellent underwater adhesion performance and good biocompatibility. Marine mussels can firmly adhere to rock surfaces in humid or underwater environments through specific proteins rich in 3,4-dihydroxyphenylalanine (DOPA), and the catechol structure in the DOPA molecule plays a key role in forming strong interactions. Currently, the synthesis of traditional mussel-inspired adhesives mainly relies on monomers derived from fossil resources, which usually requires harsh conditions, a cumbersome process, and a heavy environmental burden. In addition, although mussel-inspired adhesives exhibit excellent adhesion performance in underwater environments, their stability in low-temperature and organic solvent environments is still insufficient. Therefore, constructing a mussel-inspired adhesive system that is sustainable in origin and has high adhesion and good resistance to extreme environments is still a severe challenge in the field of material design and synthesis.

[0003] Lignin, as one of the main components of biomass, accounts for about 30% of the total organic carbon on Earth, and is the most abundant renewable aromatic carbon resource in nature. Through catalytic degradation technology, lignin can be directionally converted into easily purified aromatic monomers, and the product type is closely related to the catalytic system and the structural characteristics of lignin itself. The controllability of lignin degradation monophenol structure provides a new opportunity for its high-value utilization in the field of sustainable chemicals and functional materials. Existing research has shown that lignin-derived monophenols can be used as sustainable alternatives to petroleum-based aromatic compounds to construct structure-controllable polymer materials. However, existing strategies often generate chemically inert polymers, i.e., the key functional groups such as phenolic hydroxyl groups and methoxyl groups in lignin are consumed in the polymerization process, so that the polymer only has basic structural support function and lacks specific physicochemical properties. This greatly limits the further application of lignin degradation monophenols in the field of functional polymers. Therefore, developing lignin high-value utilization paths around the design of functional polymers, such as constructing mussel-inspired adhesion materials, not only conforms to the green and sustainable development concept, but also is expected to greatly enhance its application potential.

[0004] A previous study (Nat. Commun. 2019, 04, 2041-1723) reported a plant-inspired hydrogel adhesive based on Ag-lignin nanoparticles. This system constructs a dynamic catechol redox system, creating a continuous reduction-oxidation cycle within the hydrogel network, thus endowing the material with long-term reversible adhesion. However, under dry conditions, the maximum adhesion strength of this material is only about 110 kPa, indicating insufficient overall adhesion performance. In contrast, a previous study (Chem. Eng. J. 2024, 482, 148828) reported a mussel-inspired underwater adhesive material constructed from C-lignin-derived catechol monomers from plant shells. This material exhibits excellent adhesion performance on various media surfaces (glass, wood, PTFE, steel plate), especially with an adhesion strength exceeding 2.0 MPa on hydrophobic PTFE and an underwater adhesion strength exceeding 8.1 MPa on steel plate. CN120059670A discloses a lignin-based adhesive, which is obtained by mixing L-malic acid and β-cyclodextrin to obtain a eutectic solvent. Biomass and the eutectic solvent are mixed, vacuum filtered, and the filtrate is collected to obtain a lignin and DES mixed liquid. The mixture is heated to a viscous state to obtain the lignin-based adhesive. CN105793272A discloses a method for treating lignin and preparing an adhesive composition. The method includes the following steps: a) dissolving lignin in an aqueous composition, the composition comprising a compound selected from phenols and a base, while maintaining the temperature of the composition at 40-85°C, wherein the base comprises an alkali metal hydroxide; b) heating the composition at a temperature higher than the temperature of the composition in step a), wherein the temperature of the composition does not exceed 100°C, while maintaining the pH value of the composition at 6-14; and c) mixing the composition formed in step b) with a crosslinking agent and heating the composition at a temperature of 60-100°C, while maintaining the pH value of the composition at 6-14.

[0005] Although the above studies have made significant progress in improving the performance of lignin-based biomimetic adhesives, there are currently no reports in the literature on the development of biomimetic functional materials that maintain high adhesion performance in extreme environments (such as underwater ultra-low temperatures, organic solvents, etc.) by using lignin-degraded monophenols as direct building blocks. Summary of the Invention

[0006] To address the issue of weak adhesion in existing lignin-based adhesives, particularly in extreme environments such as underwater cryogenics and organic solvents, this invention proposes an adhesive based on lignin-degraded monophenols as direct building blocks. This adhesive maintains excellent adhesion performance under various environmental and even extreme conditions (such as cryogenics and organic solvents), promoting the high-value application of lignin-degraded monophenols in high-performance biomimetic materials. Specifically, this invention proposes a "depolymerization-derivation-copolymerization" strategy for preparing high-performance biomimetic adhesives: using wood G / S-lignin-degraded monophenols and plant shell C-lignin-degraded monophenols, namely propoxymonophenol and propanol-catechol, as raw materials, a series of adhesive materials P(C) with mussel biomimetic properties are prepared through steps such as functionalization modification of degraded monophenols and free radical copolymerization. x - co -G y ), where x molar content is 10-40% and y molar content is 60-90%. Performance tests show that P(C) 0.4 - co -G 0.6 The adhesive material exhibits excellent adhesion performance in humid and extremely cold environments, with an underwater adhesion strength of up to 8.7 MPa and maintaining a bond strength of over 7.3 MPa even at -196℃. After alternating cycles of seawater and liquid nitrogen, its adhesion strength still reaches 5.7 MPa. Furthermore, this adhesive maintains good adhesion performance in acidic and alkaline environments and common organic solvents, reaching approximately 8 MPa and 4 MPa respectively, and can be efficiently recovered and reused through dichloromethane treatment. This invention addresses the problem that existing bio-based adhesives struggle to maintain excellent and stable adhesion performance in extreme environments such as underwater and ultra-low temperatures, and are generally difficult to recycle and reuse.

[0007] To achieve the above objectives, the present invention provides the following technical solution: The first objective of this invention is to provide a multi-layered weather-resistant lignin monomer-based adhesive, which is a random copolymer composed of repeating units C and G, wherein the number of repeating units C accounts for 35-45%. .

[0008] Preferably, the number of repeating units C accounts for 36-44%, such as 37-43%, 38-42%, 39-41%, and most preferably, the number of repeating units C accounts for 40%.

[0009] Furthermore, the number average molecular weight of the lignin monomer-based adhesive is 15 × 10⁻⁶. 3 -30×10 3 Preferably, the number average molecular weight of the lignin monomer-based adhesive is 20 × 10⁻⁶. 3-25×10 3 For example, 21×10 3 22×10 3 23×10 3 24×10 3 .

[0010] Among numerous polymers based on lignin-degraded monophenol monomers, the inventors discovered that only copolymers prepared from plant shell C-lignin-degraded monophenol (propanol-catechol) and wood G-lignin-degraded monophenol (guaiacol, propanol) in a specific ratio exhibited the best adhesive strength and multiple weather resistance properties. Other monomers, such as wood S-lignin-degraded monophenol (eugenol), MC monomer, and H monomer, could not achieve the adhesive strength and weather resistance of the random copolymer of repeating units C and G in a specific ratio.

[0011] This invention also provides a method for preparing the above-mentioned multi-weather-resistant lignin monomer-based adhesive, comprising the following steps: Monomer C and monomer G are free radical polymerized under initiator conditions. The resulting copolymer undergoes deprotection of the benzyl group on monomer C to obtain a multi-weather-resistant lignin monomer-based adhesive. .

[0012] Furthermore, the molar ratio of monomer C to monomer G is 35-45:55-65, such as 38-42:58-62, 39-41:59-61. In a preferred embodiment of the present invention, the molar ratio of monomer C to monomer G is 40:60.

[0013] Further, the copolymerization reaction medium is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; the initiator is selected from azo initiators and peroxide initiators; the azo initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovalerate, azobiscyclohexylformitrile, dimethyl azobisisobutyrate, and azobiscyanopentanoic acid; the peroxide initiator is selected from at least one of benzoyl peroxide, dicumyl peroxide, tert-butyl hydroperoxide, lauroyl peroxide, tert-butyl peroxyvalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxide, and dicyclohexyl peroxide; the amount of initiator added is 3-10 mol of the monomer amount.

[0014] Furthermore, the copolymerization reaction was carried out at 55-75℃ for 8-12 hours. After the reaction, unreacted monomers and solvents were removed by a sedimentation-purification step to obtain the hydroxyl-protected intermediate P(C) x - co -G yThe condition for deprotection is that the intermediate product P(C)-Bn. x - co -G y )-Bn is dissolved in an organic solvent, and a deprotecting agent is slowly added under certain conditions. The temperature is raised to room temperature to carry out the deprotection reaction. After the reaction is completed, extraction, rotary evaporation, and washing are performed sequentially to obtain a yellow gel-like substance, which is the product, P(C) multi-weather-resistant lignin monomer-based adhesive. x - co -G y The ratio of x to y is 35-45:55-65, for example, 38-42:58-62, 39-41:59-61.

[0015] Further, the deprotection process involves slowly adding the deprotecting agent dropwise at 0-5°C (over 10-30 minutes), and then slowly raising the temperature to room temperature for the deprotection reaction (over 10-30 minutes). After the deprotection reaction is complete, extraction, rotary evaporation, and washing are performed sequentially to obtain a pale yellow gel-like substance, which is copolymer P(C x - co -G y The product is a multi-weather-resistant lignin monomer-based adhesive. Furthermore, the deprotecting agent is at least one of trimethyliodosilane, tetrabutylammonium fluoride, or trifluoroacetic acid, and the deprotection is carried out under an inert atmosphere, namely nitrogen and / or argon.

[0016] Testing revealed that monomers C and G have similar reactivity, and their copolymerization yields a random copolymer. The inventors also attempted to prepare a block copolymer by first adding monomer C, reacting for 6 hours, and then adding monomer G and continuing the reaction for another 6 hours, but the resulting block copolymer exhibited poor adhesion properties.

[0017] Furthermore, the synthetic route for monomer C is as follows: .

[0018] Furthermore, monomer C is prepared by a method comprising the following steps: (S1)C-lignin source was catalytically depolymerized in an alcohol solvent under a hydrogen atmosphere at 160-240℃ under the action of a heterogeneous metal catalyst. The catalyst was removed by filtration and the volatiles were removed by evaporation to obtain an oily lignin product. After purification by silica gel column chromatography, a white solid product POH-C was obtained. (S2) POH-C and the protective reagent benzyl bromide reacted in the presence of potassium carbonate. The inorganic salts were removed by filtration, the volatiles were removed by evaporation, and the crude product was purified by silica gel column chromatography to obtain a yellow solid POH-C-Bn. (S3) POH-C-Bn and acryloyl chloride react in the presence of an acid-binding agent. After the reaction is complete, the volatiles are removed by evaporation and purified by silica gel column chromatography to obtain a light yellow oily product POH-CA, i.e. monomer C.

[0019] Further, in step (S1), the C-lignin source is selected from at least one of castor bean shell, tallow tree shell, jatropha fruit shell, nutshell, and camellia shell; the heterogeneous metal catalyst is at least one of Pd / C, Ru / C, Pt / C, Ni / C, and X / ZnO / C, wherein X is Ru, Pd, or Co; the alcohol solvent is selected from methanol and ethanol; the ratio of alcohol solvent to C-lignin source is 50-100 mL: 1 g; the hydrogen pressure is 2-5 MPa, the reaction temperature is 180-220℃, and the reaction time is 1-5 h; the elution solvent for silica gel column chromatography purification is ethyl acetate and petroleum ether at a volume ratio of 1-3:1. -3 mixed solvent; in step (S2), the molar ratio of POH-C, benzyl bromide, and potassium carbonate is 1:2-2.5:2.8-3.5, preferably 1:2.2-2.5:3-3.2, and the elution solvent for silica gel column chromatography purification is a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1-3:1-3; in step (S3), the acid-binding agent is an amine compound, such as triethylamine, tripropylamine, or pyridine; the molar ratio of POH-C, acryloyl chloride, and acid-binding agent is 1:1-1.5:1-2, preferably 1:1.25-1.35:1.4-1.6; the eluent for silica gel column chromatography purification is petroleum ether.

[0020] Furthermore, the synthetic route for monomer G is as follows: .

[0021] Furthermore, monomer G is prepared by a method comprising the following steps: (T1)G / S lignin source was catalytically depolymerized in an alcohol solvent under a hydrogen atmosphere at 160-240℃ under the action of a multiphase metal catalyst. After the reaction was completed, the mixture was cooled and depressurized. The crude lignin oil obtained was dissolved in dichloromethane, washed with water, and the solvent was removed by rotary evaporation to obtain refined lignin oil. The monomeric phenolic substances were extracted with n-hexane at 50-70℃. The extract was back-extracted with potassium hydroxide solution, concentrated, and crystallized at low temperature to obtain potassium salt crystals, namely Pr-SK salt. The remaining mother liquor was acidified and purified by silica gel column chromatography to obtain Pr-G. Because the S monomer is more likely to form potassium salt with potassium hydroxide solution, the solubility and reactivity of the two are different. (T2)Pr-G and acryloyl chloride reacted under acid-binding conditions. After the reaction was completed, the solvent was removed by rotary evaporation, and the product was purified by silica gel column chromatography to obtain a colorless oily product, Pr-GA, i.e., monomer G.

[0022] Further, in step (T1), the G / S lignin source is selected from at least one of eucalyptus, birch, poplar, pine, and fir; the multiphase metal catalyst is at least one of Pd / C, Ru / C, Pt / C, Ni / C, and X / ZnO / C, where X is Ru, Pd, or Co; the alcohol solvent is selected from methanol and ethanol; the hydrogen pressure is 2-5 MPa, the reaction temperature is 200-250℃, and the reaction time is 1-5 h; the potassium hydroxide solution concentration is 0.1-1 mol / L; in step (T2), the acid-binding agent is an amine compound, such as triethylamine, tripropylamine, or pyridine; the molar ratio of Pr-G, acryloyl chloride, and the acid-binding agent is 1:1-1.3:1-1.5.

[0023] The derivatization steps of propylphenol (monomer G) are basically the same as those of propanol-catechol (monomer C). The main difference is that the former does not require hydroxyl protection because its molecular structure does not contain ortho-phenolic hydroxyl groups that are easily oxidized or participate in side reactions. Monomer C, however, contains hydroxyl groups, and before polymerization, hydroxyl groups are actually protected with benzyl groups, etc., and then deprotected after copolymerization.

[0024] This invention provides a method for preparing a lignin monomer-based biomimetic adhesive that exhibits excellent adhesive properties even under extreme environmental conditions. The method uses wood G / S-lignin and plant shell C-lignin-degraded monophenols (propyl monophenol and propanol-catechol) as raw materials. Through steps such as functionalization modification of the degraded monophenols and free radical copolymerization, a series of adhesive materials with mussel-inspired biomimetic properties are prepared. This adhesive material exhibits excellent adhesive performance in humid and extremely cold environments, with an underwater adhesion strength reaching 8.7 MPa and maintaining a bond strength of over 7.2 MPa even at -196℃ ultra-low temperature conditions. It also possesses good organic solvent resistance and recyclability. Compared with existing lignin-based biomimetic adhesive materials, the adhesive material prepared by this invention exhibits excellent tolerance under extreme conditions, making it highly innovative.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The adhesive prepared by this invention exhibits excellent adhesion performance under various environmental conditions, including complex environments such as dry, humid, underwater, acidic and alkaline media, and organic solvents. Even in ultra-low temperature environments, it can still maintain strong adhesion strength, which is expected to meet the requirements of adhesive performance in extreme environments in the medical, chemical and other fields.

[0026] (2) The adhesive prepared by the present invention can form a strong bond with the interface of various materials, such as steel plate, glass, aluminum plate, copper plate, mica and ceramics, and is suitable for a variety of application scenarios in life and industrial production, and has wide applicability.

[0027] (3) The adhesive prepared by the present invention has excellent recyclability and can be used repeatedly between room temperature and low temperature while maintaining a stable adhesion effect. It exhibits good weather resistance and reusability and has obvious potential for industrial application.

[0028] (4) The present invention uses natural lignin as the main raw material. The raw material is widely available, renewable, low-carbon and inexpensive, which is in line with the concept of green and sustainable development. At the same time, its preparation process is simple and easy to scale up, and has good prospects for industrial production. Attached Figure Description

[0029] To better understand the technical solutions of the embodiments of the present invention, the preferred embodiments of the present invention will be further described in detail below with reference to the accompanying drawings. However, the following accompanying drawings should not be construed as limiting the present invention.

[0030] Figure 1 The nuclear magnetic resonance H-spectrum of monomer C, the product of Preparation Example 1; Figure 2 The nuclear magnetic resonance C-spectrum of monomer C, the product of Preparation Example 1; Figure 3 The nuclear magnetic resonance H-spectrum of monomer G, the product of Preparation Example 2; Figure 4 The nuclear magnetic resonance C-spectrum of monomer G, the product of Preparation Example 2; Figure 5 It is product P(C) from Example 1 0.4 - co -G 0.6 The nuclear magnetic resonance H-spectrum of ) Figure 6 These are the DSC spectra corresponding to seven polymers with different compositions. Detailed Implementation

[0031] The present invention will be further illustrated below with reference to specific embodiments. The purpose of this illustration is only to enable those skilled in the art to better understand the present invention, and it is not intended to limit the scope of the present invention.

[0032] Unless otherwise specified, the experimental and testing methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials are commercially available.

[0033] Preparation Example 1: Preparation of Monomer C .

[0034] C-lignin (500 mg), Pd / C (150 mg), and methanol (100 mL) were added to a Parr high-pressure reactor, sealed, and purged with nitrogen, followed by hydrogen (3 MPa). The reaction was carried out at 220 °C for 4 hours. After the reaction was completed, the mixture was cooled and the pressure was slowly released. The catalyst was removed by filtration, and the volatiles were evaporated to obtain an oily lignin product. The product was purified by silica gel column chromatography (using ethyl acetate / petroleum ether as eluent) to obtain a white solid product, POH-C (200 mg), which is approximately 1.2 g of POH-C per 10 g of Sapium sebiferum seed coat. Subsequently, POH-C (1.89 g, 11.2 mmol), benzyl bromide (4.61 g, 27.0 mmol), potassium carbonate (3.9 g, 33.7 mmol), and acetonitrile (30 mL) were added to a reaction flask and reacted under reflux for 4 hours. The reaction solution was filtered to remove inorganic salts, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1) to give a yellow solid POH-C-Bn (3.6 g, 92% yield). POH-C-Bn (3.6 g, 10.3 mmol), triethylamine (1.6 g, 15.8 mmol), and anhydrous dichloromethane (30 mL) were mixed and cooled to 0°C. Acryloyl chloride (1.2 g, 13.2 mmol) was added dropwise, and the mixture was reacted overnight at room temperature. After removing volatiles by rotary evaporation, the product was purified by silica gel column chromatography (pure petroleum ether) to give a pale yellow oily product, monomer C (4.1 g, 99% yield).

[0035] Figure 1 The NMR spectrum of product monomer C is shown in Figure 1. Figure 2 It is the nuclear magnetic resonance C-NMR spectrum of the product monomer C.

[0036] Preparation Example 2: Preparation of G Monomer .

[0037] Birch wood chips (20 g, particle size 2–5 mm), RuN / ZnO / C catalyst (2 g), and methanol (200 mL) were added to a 300 mL stainless steel reactor equipped with a mechanical stirrer. After nitrogen purging to remove oxygen, hydrogen gas was introduced to 3 MPa, and the reaction was carried out at 240 °C for 4 hours. After the reaction was completed, the mixture was allowed to cool naturally and the pressure was slowly released. The soluble components (mainly lignin-derived monomers, dimers, and oligomers) and insoluble solid phases (cellulose, hemicellulose, and catalyst) were separated by filtration through a 0.22 μm filter membrane. GC analysis showed that propyl-substituted eugenol (Pr-S, 30.9 wt%) and guaiacol (Pr-G, 8.1 wt%) were the main monomers in the soluble products. The obtained lignin oil was dissolved in dichloromethane, washed with water, and the solvent was removed by rotary evaporation to obtain lignin oil. The monomeric phenols were then extracted with n-hexane at 65 °C. High-purity Pr-SK salt can be obtained by stepwise extraction, concentration and low-temperature crystallization of the extract with 0.4, 0.5 and 0.6 mol / L potassium hydroxide solution. The remaining mother liquor is then purified by silica gel column chromatography to obtain Pr-G monomer.

[0038] In a typical reaction, the obtained Pr-G monomer (5 g, 30.1 mmol), triethylamine (4.6 g, 45 mmol), and anhydrous dichloromethane (40 mL) were mixed and cooled to 0 °C. Acryloyl chloride (5.8 g, 36 mmol) was slowly added dropwise, and the reaction mixture was heated to room temperature and stirred overnight. After the reaction was complete, the solvent was removed by rotary evaporation, and the residue was purified by silica gel column chromatography (eluting with pure petroleum ether) to give a colorless oily product Pr-GA, i.e., monomer G (6.3 g, yield 96%).

[0039] Figure 3 It is the H-spectrum of the single G nuclear magnetic resonance. Figure 4 It is the nuclear magnetic resonance C spectrum of the single G.

[0040] Example 1: Comparison of adhesive properties of copolymers with different feed ratios 1. Preparation of copolymers with different feed ratios (1) Monomer C and monomer G were dissolved in N,N-dimethylformamide (DMF) at different molar ratios (C:G = 0.1:0.9, 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5). Azobisisobutyronitrile (AIBN) at 5% of the total molar amount of monomers was added as an initiator under nitrogen protection, and the reaction was carried out at 60°C for 10 hours. After the reaction was completed, unreacted monomers and residual solvent were removed by repeating the sedimentation-purification step three times to obtain the intermediate product P(C). x - co -G y )-Bn.

[0041] (2) The above polymer P(C) x- co -G y )-Bn was dissolved in anhydrous dichloromethane, and the system was cooled in an ice bath. Then, tetrabutylammonium fluoride, the deprotecting agent, was slowly added dropwise over 10 min at 0 °C, and the temperature was slowly raised to room temperature over 20 min to carry out the deprotection reaction. After the reaction was complete, extraction, rotary evaporation, and repeated washing were performed sequentially to obtain a pale yellow gel-like substance, which was the target copolymer P(C) containing the catechol backbone. x - co -G y The adhesive materials obtained with different feed ratios are denoted as P(C). 0.1 - co -G 0.9 ), P(C 0.2 - co -G 0.8 ), P(C 0.3 - co -G 0.7 ), P(C 0.4 - co -G 0.6 ), P(C 0.5 - co -G 0.5 ).

[0042] The copolymer P(C) was analyzed using gel permeation chromatography (GPC) and differential scanning calorimetry (DSC). x - co -G y The molecular weight and glass transition temperature of the copolymer were analyzed and characterized. GPC test results showed that different monomer ratios had little effect on the molecular weight of the copolymer, and the measured molecular weight was mainly distributed in the range of 18.2 × 10⁻⁶. 3 ~21.1×10 3 DSC analysis showed that the glass transition temperature (Tg) of the adhesive material gradually decreased with increasing catechol monomer (C-type) content. When the molar fraction of C-type monomer was 40%, the resulting copolymer P(C... 0.4 - co -G 0.6 The Tg of the adhesive material dropped to 3℃, indicating that it still has good flexibility and processability in low-temperature environments, laying a good foundation for the development of adhesive materials suitable for low-temperature environments.

[0043] In order to study adhesive P(C) x - co -G yTo assess the adhesion properties of samples, this invention employs the lap shear method to test the adhesion strength of all samples. This method offers advantages such as simple sample preparation, convenient operation, and wide applicability to various substrates, and is particularly suitable for evaluating adhesion properties in humid environments (such as water and phosphate-buffered saline PBS).

[0044] The specific experimental steps are as follows: Weigh the above polymer sample, dissolve it in dichloromethane to prepare a 30 mg / mL solution, and uniformly coat it onto the surface of a 100 mm × 10 mm × 1 mm steel plate, with a coating area of ​​10 mm × 10 mm and a coating thickness of 0.03 mm. Then, the two coated steel plates are bonded together, clamped with dovetail clips, and placed in a vacuum drying oven at 100℃ for 1 hour to complete curing. After curing, the sample is placed on an electronic universal testing machine for tensile testing to determine its shear adhesion strength. The results are shown in Table 1 below. The lignin monomer-based adhesive of this invention exhibits enhanced polymer molecular chain fluidity during heating, enabling it to fully wet the steel plate surface. Simultaneously, the phenolic hydroxyl structure interacts with the oxide layer on the metal surface, resulting in a stable copolymer network structure with strong moisture resistance after heat treatment and curing. The cured film forms a tough adhesion layer on the steel plate surface, achieving multiple performance requirements including strong adhesion, low-temperature resistance, and resistance to humid environments.

[0045] Experimental results show that the adhesive properties of the polymer gradually increase with the increase of catechol group (C unit) content. Specifically, P(C) 0.1 - co -G 0.9 ), P(C 0.2 - co -G 0.8 ), P(C 0.3 - co -G 0.7 ), P(C 0.4 - co -G 0.6 The adhesion strengths of the catechol groups were 2.3 MPa, 2.9 MPa, 3.6 MPa, and 8.7 MPa, respectively. This result clearly demonstrates that the catechol groups have a significant enhancing effect on improving the adhesion properties of the polymer. However, even with a large number of C units, such as P(C... 0.5 - co -G 0.5 It has already formed a gel-like state, is insoluble in any solvent, and cannot be used as an adhesive.

[0046] Figure 5 It is P(C) 0.4 - co -G 0.6 The nuclear magnetic resonance H spectrum of ).

[0047] Table 1. Copolymer P(C) x -co -G y Performance testing .

[0048] Comparative Example 1 (1) Monomer C was dissolved in N,N-dimethylformamide (DMF). Under nitrogen protection, 5% of the total molar amount of monomer C and monomer G was added as an initiator, and the reaction was carried out at 60°C for 6 hours. Then, monomer G was added, and the molar ratio of monomer C to monomer G was 0.4:0.6. The reaction was continued at this temperature for another 6 hours. After the reaction was completed, unreacted monomers and residual solvents were removed by repeating the precipitation-purification steps three times to obtain the intermediate product P(C). 0.4 - b -G 0.6 )-Bn.

[0049] (2) The above polymer P(C) 0.4 - b -G 0.6 )-Bn was dissolved in anhydrous dichloromethane, and the system was cooled in an ice bath. Then, tetrabutylammonium fluoride, the deprotecting agent, was slowly added dropwise over 10 min at 0 °C, and the temperature was slowly raised to room temperature over 20 min to carry out the deprotection reaction. After the reaction was complete, extraction, rotary evaporation, and repeated washing were performed sequentially to obtain a pale yellow gel-like substance, which was the target copolymer P(C) containing the catechol backbone. 0.4 - b -G 0.6 ). and P(C) in Example 1 0.5 - co -G 0.5 Unlike random copolymers, P(C) in Comparative Example 1 is a random copolymer. 0.4 - b -G 0.6 () is a block copolymer of monomers C and G. Under the same conditions as in Example 1, its adhesion strength under dry conditions is only 0.3 MPa. The possible reason is that the monomers in the block polymer have poor distribution and dispersion, and they restrain each other greatly, which affects the polymer properties.

[0050] Example 2: Comparison of adhesion performance of adhesive P(C0.4-co-G0.6) on different substrate surfaces The specific experimental steps are as follows: Weigh P(C) 0.4 - co -G 0.6The polymer sample was dissolved in dichloromethane to prepare a 30 mg / mL solution, which was then uniformly coated onto the surface of a 100 mm × 10 mm × 1 mm steel plate, with a coating area of ​​10 mm × 10 mm and a coating thickness of 0.03 mm. Two substrates coated with the sample were then bonded together, clamped with dovetail clips, and placed in a vacuum drying oven at 100 °C for 1 hour to complete curing. After curing, the sample was subjected to a tensile test on an electronic universal testing machine to determine its shear-adhesion strength.

[0051] Different substrate materials were tested, including steel plates, glass, copper plates, aluminum plates, ceramic sheets, mica, acrylic, and polytetrafluoroethylene (PTFE). Experimental results showed that the adhesive exhibited significantly higher adhesion strength on hydrophilic substrates (such as steel plates, glass, copper plates, aluminum plates, ceramic sheets, and mica) than on hydrophobic substrates (such as acrylic and PTFE). The highest adhesion strength was observed on steel plates. This difference primarily stems from the interaction mechanism between the active groups in the adhesive molecules and the substrate surface. On one hand, the phenolic hydroxyl groups in the polymer can form hydrogen bonds with the surface of hydrophilic substrates (such as glass and wood), thereby enhancing interfacial adhesion. On the other hand, the catechol structural units can form coordination bonds with the surface of polar metal substrates (such as steel plates), further improving adhesion strength. Furthermore, with the increase of phenolic hydroxyl content in the polymer, not only are intermolecular hydrogen bonding enhanced, increasing intramolecular cohesion, but the interfacial interaction between the polymer and the polar substrate is also improved. Ultimately, the system achieves a new synergistic balance between adhesive strength and polymer cohesive strength, resulting in excellent overall performance.

[0052] Table 2. Adhesive P(C) for different substrate surfaces 0.4 - co -G 0.6 Adhesion properties .

[0053] Example 3: Comparison of adhesive properties of adhesive P(C0.4-co-G0.6) in different humid environments Due to the diversity of practical application environments, adhesives often need to withstand different usage conditions, ranging from dry to wet, especially in complex humid environments such as seawater, acidic, or alkaline conditions. In Examples 1 and 2 above, the present invention evaluated the adhesion performance of the bio-based adhesive in a dry environment. Experimental results show that adhesive P(C 0.4 - co -G 0.6 It exhibits excellent adhesion properties on various substrates (including metals, glass, and plastics), with shear strength reaching the MPa level. To further investigate the applicability of this adhesive in humid environments, this invention simulated various humid environments (water, seawater, acidic environments, and alkaline environments), applying adhesive P(C) to...0.4 - co -G 0.6 The bonded steel plates were immersed in the above-mentioned liquids (water, seawater, hydrochloric acid solution with pH=3, and sodium hydroxide solution with pH=11) for 48 hours. After removal and drying, the adhesion strength was tested, and the results are shown in Table 3 below.

[0054] Experimental results show that this adhesive P(C) 0.4 - co -G 0.6 The polymer maintains excellent adhesion properties in various humid environments, especially in water, seawater, and acidic conditions, where its adhesion strength is almost identical to that in the dry state, indicating good environmental stability. In contrast, adhesion properties decrease in strongly alkaline environments, presumably due to partial dissociation of metal-catechol coordination bonds and hydrogen bonds under alkaline conditions, weakening interfacial adhesion. Furthermore, to assess the polymer's tolerance to organic solvents, its adhesion strength in petroleum ether and ethanol environments was further tested. The results show that the polymer maintained adhesion strengths of 4.3 MPa and 3.7 MPa in petroleum ether and ethanol, respectively, indicating that the material possesses both good broad environmental compatibility and organic solvent adaptability.

[0055] Table 3 Adhesive P(C) in different humid environments 0.4 - co -G 0.6 Comparison of Adhesion Properties .

[0056] Example 4: Comparison of the effects of lignin-degraded monophenol structures on adhesive adhesion properties To investigate the effects of the number of methoxy groups and the length of the catechol monomer side chain in G / S type monophenols on the adhesive properties of adhesives, this invention designed and synthesized four copolymer adhesives with different structures, and tested and compared their adhesive properties on steel plates.

[0057] All four adhesives mentioned use P(C) 0.4 - co -G 0.6 The same synthetic route was used, with the only adjustment being the type of comonomer, as shown below (see attached diagram for structure): Adhesive P(C) 0.4 - co -H 0.6 ): P(C 0.4 - co -G 0.6In this study, propylguaiacol (G) was replaced with propylphenol monomer (monomer H) to investigate the effect of the absence of methoxy substitution on the benzene ring. Monomer H was prepared as follows: 4-propylphenol (5 g, 36.8 mmol), triethylamine (5.6 g, 55.1 mmol), and anhydrous dichloromethane were mixed, and acryloyl chloride (4.0 g, 44.1 mmol) was added dropwise at 0 °C with stirring overnight at room temperature. After the reaction was complete, the solvent was removed by rotary evaporation, and the residue was purified by silica gel column chromatography (eluting with pure petroleum ether) to obtain a colorless oily product, Pr-HA (6.8 g, yield 97%).

[0058] P(C 0.4 - co -H 0.6 The structural diagram is as follows: .

[0059] It is understandable that although the structural expression is block co-aggregation, it is only for the convenience of expression, and the specific distribution of its repeating units is not clear.

[0060] Adhesive P(C) 0.4 - co -S 0.6 ): P(C 0.4 - co -G 0.6 The monomer G in the reaction was replaced with 2,6-dimethoxypropylphenol and acryloyl chloride to form the monomer S (S monomer), which was used to evaluate the effect of the dimethoxy substitution on the benzene ring. P(C 0.4 - co -S 0.6 The structural formula is as follows: .

[0061] Adhesive P (MC) 0.4 - co -G 0.6Monomer C was replaced with monomer MC, obtained from the reaction of methanol-based catechol and acryloyl chloride, to analyze the effect of side chain length on adhesive properties. Monomer MC was prepared as follows: 3,4-dihydroxybenzaldehyde MC (7 g, 50.7 mmol), benzyl bromide (19 g, 111.5 mmol), potassium carbonate (17.5 g, 126.7 mmol), and acetonitrile (50 mL) were added to a reaction flask and reacted under reflux for 4 hours. After the reaction, inorganic salts were removed by filtration, and acetonitrile was removed by rotary evaporation. The residue was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1) to obtain a yellow solid product PO-MC-Bn (15.3 g, 95% yield). Subsequently, PO-MC-Bn (5.8 g, 18.2 mmol), LiAlH4 (2.1 g, 54.7 mmol), and tetrahydrofuran (60 mL) were added to a reaction flask and reacted at 0°C for 6 hours under nitrogen protection. After the reaction was complete, ice water was added dropwise to terminate the reaction, followed by the addition of concentrated hydrochloric acid until the solution changed color. The solution was extracted sequentially with dichloromethane and saturated brine to remove water, then concentrated by rotary evaporation. The residue was purified by silica gel column chromatography (petroleum ether: ethyl acetate = 1:1) to give a white solid POH-MC-Bn (5.7 g, 98% yield). Subsequently, POH-MC-Bn (1.6 g, 5 mmol), triethylamine (0.8 g, 7.5 mmol), and anhydrous dichloromethane (50 mL) were mixed and cooled to 0°C. Acryloyl chloride (0.6 g, 6 mmol) was slowly added dropwise, and the mixture was stirred overnight at room temperature. After the reaction was complete, the solvent was removed by rotary evaporation, and the residue was purified by silica gel column chromatography (eluting with pure petroleum ether) to give a colorless oily product POH-MCA (1.8 g, 94% yield).

[0062] P(MC 0.4 - co -G 0.6 The structural formula is as follows: .

[0063] Adhesive P(C) 0.4 - co -S 0.4 / G 0.2 ): By replacing monomer G with monomer S, the influence of copolymerization ratio and functional group synergy on adhesion performance was further investigated.

[0064] P(C 0.4 - co -S 0.4 / G 0.2 The structural formula is as follows: .

[0065] Figure 6These are DSC spectra of seven polymers with different compositions. It can be seen that the copolymer P(C) 0.4 - co -G 0.6 The Tg of the adhesive material dropped to 3℃, indicating that the material still has good flexibility and processability at low temperatures.

[0066] Experimental results show that adhesive P(C) 0.4 - co -S 0.6 ), P(C 0.4 - co -H 0.6 ), P(C 0.4 - co -S 0.4 / G 0.2 The adhesion properties of the three adhesives were 2.9 MPa, 6.5 MPa, and 6.1 MPa, respectively, all lower than those of adhesive P(C). 0.4 - co -G 0.6 This indicates that changes in the methoxyl content of the copolymer have a significant regulatory effect on its adhesive properties. Further comparison revealed that adhesive P(MC) 0.4 - co -G 0.6 The adhesive strength of the polymer is the lowest, mainly because the side chain of the methanol-based catechol monomer used is relatively short, which leads to a decrease in the degree of cross-linking between polymer molecules, a weakening of cohesive force, and ultimately a decrease in overall adhesive performance.

[0067] Table 4 Comparison of adhesive properties of adhesives with different lignin monomers .

[0068] Example 5: Comparison of Adhesive Performance of Different Adhesives under Extreme Conditions To further evaluate the suitability of the adhesive in harsh environments, this embodiment designed three sets of extreme condition tests: 1) testing its performance in an ultra-low temperature environment (-196℃); 2) simulating humid and cold conditions by immersing the sample in water before conducting a low-temperature test; and 3) examining its weather resistance through a "room temperature-low temperature" cycle experiment. Through this series of systematic tests, the adhesion performance of the adhesive on steel plates under different extreme conditions was analyzed in depth.

[0069] Mussel-like adhesives exhibit excellent adhesion properties in ultra-low temperature environments, primarily due to metal coordination. However, research on the performance of mussel-like adhesives that do not rely on metal coordination in extreme low-temperature environments remains limited. Lignin monomer-based adhesives contain propylene linking units, propyl groups, and methoxy groups, which not only endow the polymers with good flexibility but also give them excellent water resistance and ultra-low temperature resistance. As shown in Table 5, at a liquid nitrogen temperature of -196℃, the four adhesives P(C 0.4 - co -G 0.6 ), P(C 0.4 - co -S 0.6 ), P(C 0.4 - co -H 0.6 ), P(C 0.4 - co -S 0.4 / G 0.2 The adhesion properties of the adhesives were 7.3 MPa, 2.5 MPa, 2.4 MPa, and 4.8 MPa, respectively. Among them, the adhesive P(C) 0.4 - co -G 0.6 It exhibits superior adhesion properties. This breakthrough discovery indicates that the material has significant potential applications in extreme environments such as polar equipment maintenance and superconducting device packaging.

[0070] Table 5. Adhesion strength of different adhesives at -196℃ under extreme conditions .

[0071] Then, under simulated humid and cold conditions (the steel plate with the adhesive applied was first soaked in water for 24 hours, and then immersed in liquid nitrogen to lower the temperature to -196℃), the adhesive performance of the adhesive was analyzed. As shown in Table 6, the adhesive properties of the four adhesives P(C) were analyzed. 0.4 - co -G 0.6 ), P(C 0.4 - co -S 0.6 ), P(C 0.4 - co -H 0.6 ), P(C 0.4 - co -S 0.4 / G 0.2 The adhesion properties of the adhesives were 5.7 MPa, 2.1 MPa, 1.9 MPa, and 2.2 MPa, respectively. Among them, the adhesion properties of adhesive P(C) were... 0.4 - co -G0.6 The lignin monomer-based adhesive exhibits the best adhesion properties, indicating that the lignin monomer-based adhesive prepared in this invention has broad application prospects in humid and cold environments.

[0072] Table 6 Adhesion strength of different adhesives under humid and cold conditions .

[0073] Finally, to evaluate the adhesive P(C) 0.4 - co -G 0.6 To improve the weather resistance of P(C), this invention designed a "room temperature-ultra-low temperature" alternating cycle test scheme. During the test, the sample was subjected to 10 cycles alternating between 25℃ (room temperature, 2h) and -196℃ (liquid nitrogen temperature, 2h). Table 7 shows the experimental results, indicating that P(C) exhibits good weather resistance. 0.4 - co -G 0.6 It exhibits excellent stability under extreme temperature alternation conditions, with no significant performance degradation observed. This characteristic gives it a significant advantage in extreme environment applications such as aerospace.

[0074] Table 7 Adhesion strength of different adhesives under alternating room temperature-ultra-low temperature conditions .

[0075] In summary, the present invention provides a multi-weather-resistant lignin monomer-based adhesive, particularly P(C) 0.4 - co -G 0.6 It exhibits excellent adhesion strength to a variety of substrates and multiple weather resistances to various humid environments (organic solvents, acids, alkalis), ultra-low temperatures (-196℃), and alternating temperature-ultra-low temperature conditions, making it highly valuable for industrial applications.

Claims

1. A multi-weather-resistant lignin monomer-based adhesive, characterized in that, It is a random copolymer composed of repeating units C and repeating units G, with repeating units C accounting for 35-45% of the total. 。 2. The multi-weather-resistant lignin monomer-based adhesive according to claim 1, characterized in that, The number of repeating units C accounts for 36-44%.

3. The multi-weather-resistant lignin monomer-based adhesive according to claim 1, characterized in that, The number of repeating units C accounts for 39-41%.

4. The multi-weather-resistant lignin monomer-based adhesive according to claim 1, characterized in that, The number average molecular weight of the lignin monomer-based adhesive, as a percentage of the number of repeating unit C, is 15 × 10⁻⁶. 3 -30×10 3 .

5. A method for preparing the multi-weather-resistant lignin monomer-based adhesive according to any one of claims 1-4, characterized in that, Includes the following steps: Monomer C and monomer G undergo free radical copolymerization under initiator conditions. The resulting copolymer is then deprotected by the benzyl group on monomer C to obtain a multi-weather-resistant lignin monomer-based adhesive. 。 6. The preparation method according to claim 5, characterized in that, The copolymerization reaction medium is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; the initiator is selected from azo initiators and peroxide initiators; the azo initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovalerate, azobiscyclohexylformitrile, dimethyl azobisisobutyrate, and azobiscyanopentanoic acid; the peroxide initiator is selected from at least one of benzoyl peroxide, dicumyl peroxide, tert-butyl hydroperoxide, lauroyl peroxide, tert-butyl peroxyvalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxide, and dicyclohexyl peroxide; the amount of initiator added is 3-10 mol of the monomer amount.

7. The preparation method according to claim 5, characterized in that, The copolymerization reaction was carried out at 55-75℃ for 8-12 hours. After the reaction, unreacted monomers and solvents were removed by sedimentation-purification steps to obtain the hydroxyl-protected intermediate P(C) x - co -G y )-Bn; then deprotection is performed, and the deprotection condition is that the intermediate product P(C) x - co -G y )-Bn is dissolved in an organic solvent and undergoes a deprotection reaction. After the reaction is completed, extraction, rotary evaporation and washing are performed in sequence to obtain a yellow gel-like substance, which is the product, multi-weather-resistant lignin monomer-based adhesive.

8. The preparation method according to claim 7, characterized in that, The deprotection is in the range of 0-5. o Add the deprotecting agent dropwise over 10-30 minutes at C (add within 10-30 minutes, then raise to room temperature for 10-30 minutes to carry out the deprotection reaction). After the deprotection reaction is complete, perform extraction, rotary evaporation, and washing sequentially to obtain a pale yellow gel-like substance, which is copolymer P(C x - co -G y ), namely, the product is a multi-weather-resistant lignin monomer-based adhesive.

9. The preparation method according to claim 5, characterized in that, The synthetic route for monomer C is as follows: ; and / or The synthetic route for monomer G is as follows: 。 10. The preparation method according to claim 5, characterized in that, Monomer C is prepared by a method including the following steps: (S1)C-lignin source was catalytically depolymerized in an alcohol solvent under a hydrogen atmosphere at 160-240℃ under the action of a heterogeneous metal catalyst. The catalyst was removed by filtration and the volatiles were removed by evaporation to obtain an oily lignin product. After purification by silica gel column chromatography, a white solid product POH-C was obtained. (S2) POH-C and the protective reagent benzyl bromide reacted in the presence of potassium carbonate. The inorganic salts were removed by filtration, the volatiles were removed by evaporation, and the crude product was purified by silica gel column chromatography to obtain a yellow solid POH-C-Bn. (S3) POH-C-Bn and acryloyl chloride react in the presence of an acid-binding agent. After the reaction is complete, volatiles are removed by evaporation, and the product is purified by silica gel column chromatography to obtain a light yellow oily product, POH-CA, i.e., monomer C; and / or Monomer G is prepared by a method including the following steps: (T1)G / S lignin source was catalytically depolymerized in an alcohol solvent under a hydrogen atmosphere at 160-240℃ under the action of a multiphase metal catalyst. After the reaction was completed, the mixture was cooled and depressurized. The crude lignin oil obtained was dissolved in dichloromethane, washed with water, and the solvent was removed by rotary evaporation to obtain refined lignin oil. The monomeric phenolic substances were extracted with hexane at 50-70℃. The extract was back-extracted with potassium hydroxide solution, concentrated, and crystallized at low temperature to obtain potassium salt crystals, namely Pr-SK salt. The remaining mother liquor was acidified and purified by silica gel column chromatography to obtain Pr-G. (T2)Pr-G and acryloyl chloride reacted under acid-binding conditions. After the reaction was completed, the solvent was removed by rotary evaporation, and the product was purified by silica gel column chromatography to obtain a colorless oily product, Pr-GA, i.e., monomer G.

Citation Information

Patent Citations

  • A method for treating lignin and for producing a binder composition

    CN105793272A

  • Lignin-based strong adhesive prepared from DES pretreated biomass as well as preparation method and application of lignin-based strong adhesive

    CN120059670A